Arduino Sensors Reveal Temperature-Driven Compression Fluctuations in Vehicle Engines: Sensor Arduino Mengungkap Fluktuasi Kompresi yang Didorong oleh Suhu pada Mesin Kendaraan - Fikroh, Ubaidillah; Syahrorini , Syamsudduha (Universitas Muhammadiyah Sidoarjo, 2024)
Many modern vehicles suffer from engine trouble due to decreased compression pressure, necessitating a simple and efficient measurement tool. This study develops an Arduino-based device to measure engine compression and temperature using a pressure sensor in the spark plug location and a temperature sensor in the oil gauge, with results displayed on a 16x2 I2C LCD. Testing each engine cylinder before and after heating shows that compression pressure is strongly influenced by temperature (over 80%). The tool enhances engine diagnostics, offering precise, real-time monitoring to improve vehicle maintenance and longevity. Highlight: Real-time Monitoring: Provides precise, real-time engine diagnostics. Temperature Influence: Compression pressure is 80% influenced by temperature. Enhanced Maintenance: Offers accurate compression and temperature measurements. Keywoard: Engine trouble, Compression pressure, Arduino, Pressure sensor, Temperature sensor